Arsenopyrite Oxidation with Ozone: Stoichiometry and Kinetics. (4th July 2018) - Rodríguez-Rodríguez, C.; Nava-Alonso, F.; Uribe-Salas, A.
ABSTRACT: When the recovery of precious metals by standard cyanidation is less than 80%, the ore is classified as refractory and needs an oxidizing pretreatment before cyanidation. Arsenopyrite is one of the main sulfide matrixes where occurs refractory gold. In this work, the arsenopyrite leaching in acid media was studied using ozone as an oxidizing agent. The results obtained show that arsenopyrite leaching is carried out in a stoichiometric way: one mole of Fe and one mole of S are leached by each mole of As leached. A maximum of 60% arsenopyrite leaching was obtained when 1 g (−25 µm) was submitted to acid leaching in 800 mL of 0.18 M acid solution (either chlorhydric, nitric, or sulfuric acid), mechanically stirred at 800 rpm and with the addition of 1.2 L/min oxygen gas containing 0.079 g O3 /L at 25° for 60 min. Although the apparent activation energy estimated was 4.07 kJ/mol, it is suggested that the system is controlled by chemical reaction.